Development of a Conceptual Model of Organizational Culture Engagement: A Literature Synthesis Approach - Randi Tangdialla; Dian Intan Tangkeallo; Ade Lisa Matasik (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to construct and develop a conceptual model of Organizational Culture Engagement through a literature synthesis approach. Three important steps were taken during the process: 1. Editing and rechecking the collected data, especially regarding completeness, clarity of meaning, and consistency of meaning between variables. 2. Organizing and arranging the data collected into the required structure. 3. Analyzing: applying accepted theories, methodologies, and principles to further analyze the results of data organization to reach conclusions that answer the research objectives. According to the study's findings, employee engagement and organizational culture dimensions interact to generate organizational culture engagement. The work environment that affects employee behavior and attitudes is shaped by aspects of organizational culture, including roles, accomplishments, support, innovation and risk-taking, attention to detail, results orientation, people orientation, team orientation, stability, and aggressiveness.